Identification of the integrity index in local governments in Java - Intiyas Utami; Gideon Felix Gunawan; Gracella Theotama; Aprina Nugrahesthy Sulistya Hapsari; Natasia Alinsari (Journal of Contemporary Accounting, 2023)
Decentralization system of government in Indonesia creates local governments that have their own authority. However, this may raise the risk of corruption. The high level of corruption in Indonesia obstructs goal 16 of the Sustainable Development Goals (SDGs). The disclosure of integrity through the local government websites can create public disclosure information, so the public can assess the performance of each government and mitigate corruption levels. This study aims to explore the integrity disclosure index and identify the problems in disclosing integrity through the websites. This study uses Institutional Theory with coercive isomorphism. Data was collected based on content analysis on 113 websites of local governments in Java. The result shows that the average disclosure on the websites of the local governments in Java is 64.83%. With this good disclosure of integrity, local governments in Java can support the law on public information disclosure.